Perancangan Nganjuk E-Tourism Berbasis Android Dengan Algoritma Dijkstra Untuk Pencarian Jalur Terdekat Objek Pariwisata - Karim Amrulloh, Abdul; Putra Eka Prismana, IGL (Inovate, 2019)
Nganjuk is an area that has a myriad of very beautiful tours. Some of the attractions are Sedudo Waterfall,Embung Estumulyo, Ngetos Temple and many more interesting sights worth visiting. But efforts to promotethe tourism sector from the Nganjuk regency is still limited, such as the distribution of brochures from theDepartment of Tourism in the city center at the time of the Day of Nganjuk Anniversary. Use Dijkstra'sAlgorithm method as the nearest distance counter and use the Google Maps service to present a visual map.Nganjuk Tourism Application can guide the tourists by showing the closest route on the map to the touristlocation. Seeing Nganjuk tourism potential is so great then this thesis makes the application Nganjuk Tourbased on Android. This minithesis hopes to increase the desire of tourists to visit Nganjuk and see Nganjukcultural charm that is so special.Keywords: Android, Tourism, Nganjuk, Dijkstra Algorithm